Analysis Of The Contribution Of Conventional Reaction Training Management To The Dribbling Speed Of Soccer Athletes - Abdul Quddus; Lalu Hulfian (Sekolah Tinggi Olahraga & Kesehatan Bina Guna, 2025)
Soccer is a sport that requires mastery of various basic skills, one of which is dribbling. Fast and accurate dribbling skills are crucial, especially when under pressure or during counter-attacks. Observations indicate that PS Sakra players have weaknesses in dribbling, particularly in speed and precision when handling the ball against opponents. To address this issue, this study aims to determine the effect of conventional reaction training on improving the dribbling speed of PS Sakra players. The research method used is experimental with a